Development of contact pressure distribution of PEM fuel cell's MEA using novel clamping mechanism. (15th July 2017) - Alizadeh, E.; Ghadimi, M.; Barzegari, M.M.; Momenifar, M.; Saadat, S.H.M.
Abstract: Clamping mechanisms have significant effect on the performance of polymer electrolyte membrane (PEM) fuel cells. In this paper, PEM fuel cell with new clamping mechanism is designed to study the contact pressure distribution over the active area of PEM fuel cell's membrane electrode assembly (MEA). The clamping pressure is pneumatically exerted on the PEM fuel cell assembly. A comparison between the conventional and new clamping mechanism is carried out with simulation, and the numerical results are validated against experimental investigation performed in the fuel cell technology research laboratory. The experimental results are gathered using embedded pressure measurement films in the designed single cell. The results achieved via finite element method are in good agreement with experimental results. It is concluded that the contact pressure distribution of MEA for the new clamping mechanism is more uniform than the conventional one. Highlights: New clamping mechanism is designed to improve contact pressure distribution of MEA. The clamping pressure is pneumatically exerted on the PEM fuel cell components. A comparison between the new and conventional clamping mechanisms is carried out. Simulation results are validated with experimental measurement using pressure film. Results show that the new mechanism evenly distributes contact pressure over MEA.